A class of anti-Kasha rule narrow-band blue-violet TADF materials and their applications in OLEDs
By designing a narrow spectrum blue-violet TADF material with anti-Kasha rule, using highly distorted donor-receptor structure and multiple resonance characteristics, an efficient narrow spectrum blue-violet emission is achieved, solving the problem of low color purity of existing TADF materials, and achieving high-efficiency, narrow spectrum blue-violet emission is suitable for high-definition display.
Patent Information
- Application Number
- CN202310427604.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-20
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2043-04-20
AI Technical Summary
The existing TADF materials have a wide emission spectrum and a large half-maximum width, resulting in low color purity, limiting their application in ultra-high-definition display panels, especially high-efficiency narrow-band blue-violet TADF materials, facing many challenges.
A class of narrow spectrum band blue-violet TADF materials with anti-Kasha rule were designed. Through highly distorted donor-receptor structural characteristics and multiple resonance (MR) characteristics, the two radiation transition paths of S1→S0 and S2→S0 were realized. They were radiated with MR characteristics in low polarity environment and CT characteristics in high polarity environment, overcoming the wide FWHM and spectral redshift caused by the TADF luminescence mechanism.
The high-efficiency luminescence of the narrow spectrum blue-violet TADF material is achieved. The external quantum efficiency of the device reaches 9.61%, the y-value of the color coordinate is less than 0.05, the half-maximum width is 33nm, and the color purity is high, creating conditions for high-definition display.
Smart Images

Figure BDA0004189107820000031 
Figure BDA0004189107820000032 
Figure BDA0004189107820000061
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of luminescence and display lighting, and specifically relates to an organic blue-violet luminescent material comprising oxygen-bridged triphenylboron-dicarbazole phenylene-spiroacridine fluorene and its application in organic electroluminescent devices (OLEDs). Background Art
[0002] Organic light-emitting diodes (OLEDs) are known as a new generation of display technology and have been widely used in small and medium-sized displays. Compared with liquid crystal displays, OLEDs have clearer color purity, wider color gamut, larger viewing angles and higher contrast, and do not require any backlight units. They can achieve a variety of lightweight forms, including foldable, rollable and transparent displays. They are the display technology with the most development potential today.
[0003] Thanks to the sustainable development of material chemistry, device physics and manufacturing technology, the performance, durability and manufacturability of OLEDs have been greatly improved, but there are still some pressing challenges. In 2012, the International Telecommunication Union promulgated the Rec.2020 color gamut standard, in which the CIE coordinates of the three primary colors of red (R), green (G) and blue (B) are (0.708, 0.292), (0.170, 0.797) and (0.131, 0.046) respectively. This puts forward unprecedented quality requirements for the display color gamut standard. The light-emitting layer is the most important part of OLED, and its materials play a decisive role in the performance of OLED (light color, efficiency, life, brightness, etc.). Developing light-emitting materials that meet the Rec.2020 color gamut standard and have a narrow half-width (FWHM) is the key to solving the above color gamut problems.
[0004] In recent years, organic thermally activated delayed fluorescence (TADF) materials have become one of the most promising new luminescent materials because they can effectively realize the conversion of triplet excitons to singlet excitons through the reverse intersystem crossing (RISC) process and obtain nearly 100% internal quantum efficiency. Generally, organic TADF materials use DA configuration to reduce the overlap between HOMO / LUMO, thereby producing the smallest ΔE ST However, the intramolecular charge transfer (ICT) property of TADF materials easily leads to structural relaxation in the excited state, and exhibits a large Stokes shift, a wide emission spectrum, and a large full width at half maximum (FWHM). A large FWHM easily leads to low color purity, which is not conducive to the application of organic TADF materials in ultra-high-definition display panels.
[0005] Compared with red and green light, efficient narrow-band blue-violet TADF luminescent materials, especially narrow-band blue-violet TADF materials with color coordinate y values less than 0.05, still face many challenges. The main reasons are as follows: (1) High-energy host materials and transport layers are very scarce; (2) Long-lived triplet excitons affect the stability and efficiency roll-off of TADF-OLEDs; (3) The low RISC process of blue-violet materials easily leads to exciton annihilation; (4) Most blue-violet TADF materials exhibit a wide electroluminescence spectrum with a FWHM greater than 50nm, showing poor color purity, which hinders their application in OLED displays. Therefore, the development of new and efficient blue-violet TADF materials with narrow FWHM is urgent. Summary of the invention
[0006] In order to overcome the problems existing in the prior art, the present invention designs a class of anti-Kasha rule narrow-band blue-violet TADF materials, which perfectly integrate the highly twisted donor-acceptor structural characteristics and multiple resonance (MR) characteristics, and have two radiation transition pathways S1→S0 and S2→S0 in the excited state. In a low-polarity environment, it radiates light with MR characteristics (S2→S0), and in a high-polarity environment, it radiates light with CT characteristics (S1→S0). This class of materials overcomes the wide FWHM and spectral red shift caused by the TADF luminescence mechanism, and realizes the efficient luminescence of narrow-band blue-violet TADF materials and their application in organic electroluminescent diodes.
[0007] The invention uses 2,12-di-tert-butyl-5,9-dioxa-13b-boronaphtho[3,2,1-de]anthracene with MR characteristics as an acceptor, introduces carbazole and spiroacridinefluorene with different donor strengths through phenyl π bridge, and constructs a class of narrow-band blue-violet light materials that are anti-Kasha rule.
[0008] The present invention provides a class of anti-Kasha rule narrow-band blue-violet TADF materials having the structural characteristics shown in formula (1):
[0009]
[0010] in:
[0011] R is independently selected from hydrogen or tert-butyl.
[0012] The specific structure of the preferred anti-Kasha rule narrow-band blue-violet TADF material is as shown in formula (2):
[0013]
[0014] Another object of the present invention is to provide an application of this type of organic blue-violet luminescent material, using it as a guest luminescent material of a luminescent layer to prepare a blue-violet OLED to improve the luminescent color purity, luminescent efficiency and service life of the device.
[0015] The near-ultraviolet OLED device structure of the present invention is: ITO / PEDOT:PSS / mCPCN:x wt% emitter / TmPyPB / LiF / Al.
[0016] Among them, indium tin oxide (ITO) glass is the anode material, PEDOT:PSS is the hole injection layer material, mCPCN is the main material of the light-emitting layer, TmPyPB is the electron transport layer material, LiF is the electron injection layer material, and metal aluminum (Al) is the cathode material.
[0017] Preferably, it is: ITO / PEDOT:PSS (40nm) / mCPCN: x wt% emitter (25nm) / TmPyPB (45nm) / LiF / Al, wherein x wt% is the doping concentration of the blue-violet light-emitting material in mCPCN, which is 0.5-2wt%.
[0018] In the preferred application method, the organic blue-violet luminescent material compound 1 is used to prepare the luminescent layer of OLEDs, the doping concentration in mCPCN is 1wt%, and the external quantum efficiency is 9.61%, the color coordinates are (0.164, 0.045), and the FWHM is 33nm.
[0019] Compared with the existing technology, the beneficial effects of the present invention are:
[0020] (1) The organic blue-violet light-emitting material of the present invention has a simple molecular structure and low preparation cost.
[0021] (2) The organic blue-violet light-emitting material of the present invention has multi-channel light-emitting behavior, which overcomes the spectral red shift and spectral broadening caused by the strong ICT characteristics of the current traditional TADF materials. This is the first TADF material with narrow-band blue-violet light emission and multi-channel light-emitting behavior. The material has high luminous efficiency and high color purity, creating conditions for high-definition display. The research results show that its solution-processed OLED device highlights the characteristics of high luminous efficiency and excellent color purity. The electroluminescent peak of the device is at 410nm, the luminous efficiency is as high as 9.61%, the half-peak width is only 33nm, and the color coordinate y-axis is only 0.045, which has attractive application prospects.
[0022] (3) The organic blue-violet light-emitting material of the present invention has high thermal stability and good film-forming performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1This is a schematic diagram of the optimal structure of compound 1 in Example 1 of the present invention.
[0024] Figure 2 This is the frontier orbital distribution, energy level arrangement, SOC and NTO analysis of compound 1 in Example 1 of the present invention.
[0025] Figure 3 This is the thermogravimetric (TG) diagram of compound 1 in Example 1 of the present invention.
[0026] Figure 4 The UV-visible absorption spectrum, photoluminescence spectrum and low-temperature fluorescence phosphorescence spectrum of compound 1 in Example 1 of the present invention in toluene solution are shown.
[0027] Figure 5 It is a UV-visible absorption spectrum of compound 1 in Example 1 of the present invention in n-hexane, toluene, butyl ether, isopropyl ether, ethyl ether, ethyl acetate, tetrahydrofuran, dichloromethane, acetone and acetonitrile solutions.
[0028] Figure 6 The photoluminescence spectra of compound 1 in Example 1 of the present invention in n-hexane, toluene, butyl ether, isopropyl ether, ethyl ether, ethyl acetate, tetrahydrofuran, dichloromethane, acetone and acetonitrile solutions are shown in FIG.
[0029] Figure 7 This is a graph showing the instantaneous lifetime of compound 1 in Example 1 of the present invention in a 1% doped mCPCN film.
[0030] Figure 8 This is a graph showing the relationship between the current density and the maximum external quantum efficiency of the organic electroluminescent device doped with compound 1 in Example 1 of the present invention.
[0031] Fig. 9 This is the electroluminescence spectrum of the organic electroluminescent device doped with compound 1 in Example 1 of the present invention. DETAILED DESCRIPTION
[0032] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments and drawings. It should be understood by those skilled in the art that the specific contents described below are illustrative rather than restrictive, and the protection scope of the present invention cannot be limited thereby.
[0033] In the present invention, the preparation methods are conventional methods unless otherwise specified, and the raw materials used can be obtained from public commercial channels unless otherwise specified.
[0034] Example 1
[0035] Preparation of compound 1
[0036] The specific synthetic route of compound 1 of the present invention is as follows:
[0037]
[0038] Dissolve compound 1a (5g, 15.68mmol), compound 1b (8.76g, 31.36mmol), and cesium carbonate (15.33g, 47mmol) in 200mL N,N-dimethylformamide solution, and heat to 120°C under nitrogen protection, and stir to react overnight. Cool to room temperature, add 300mL of deionized water to the mixture, stir for 10min, and a white precipitate will appear. Filter to obtain a white precipitate, transfer the precipitate to a beaker, add a little methanol, beat for 20min, filter, and vacuum dry for 8h to obtain a white solid compound M1 (11.5g, 87%). 1 H NMR (400MHz, CDCl3) δ8.15(t,J=1.9Hz,4H),7.92(d,J=1.7Hz,2H),7.53(dt,J=8.6,1 .8Hz,4H),7.14(dd,J=8.6,1.9Hz,4H),1.47(s,36H).MALDI-MS(m / z):calcd.836.72 found.836.71.
[0039] Under nitrogen conditions, compound M1 (1g, 1.19mmol), compound 1c (0.40g, 1.19mmol), tris(dibenzylideneacetone)dipalladium (22mg, 0.03mmol), 1,1'-bis(diphenylphosphino)ferrocene (DPPF) (27mg, 0.05mmol), sodium tert-butoxide (0.23g, 2.38mmol) were dissolved in 50mL toluene, heated to 80°C, stirred for 12h, and then cooled to room temperature. The mixture was filtered through diatomaceous earth and silica, and concentrated under reduced pressure. The concentrate was purified by silica gel column chromatography (dichloromethane / petroleum ether = 1 / 4, v / v) to obtain a white solid M2 (0.45g, 36%). 1 H NMR (400MHz, CDCl3) δ8.14-8.05(m,4H),7.78-7.63(m,4H),7.57-7.44(m,5H),7.36-7.18(m,7H),7.06(dt,J=2 4.3,7.2Hz,4H),6.69-6.49(m,4H),6.41-6.31(m,2H),1.40(d,J=4.7Hz,36H).MALDI-MS(m / z):calcd.1041.23 found.1041.22.
[0040] Compound M2 (0.4 g, 0.38 mmol), compound 1d (0.20 g, 0.40 mmol), Pd(PPh3)4 (14 mg, 0.01 mmol), potassium carbonate (0.11 g, 0.77 mmol) were dissolved in a mixed solvent of tetrahydrofuran and water (20 mL: 5 mL). Under nitrogen protection, the mixture was heated to 80 ° C and stirred for 24 h. After cooling to room temperature, 50 mL of deionized water was added to the mixture, and the reaction mixture was extracted with dichloromethane (3×50 mL), dried over anhydrous sodium sulfate, and the solvent was removed by vacuum distillation. The residue was separated and purified by silica gel column chromatography (petroleum ether / dichloromethane=5 / 1, v / v) to obtain a white solid compound 1 (0.35 g, 68%). 1 H NMR(400MHz, CDCl3)δ8.48(d,J=2.6Hz,2H),7.99-7.92(m,4H),7.88-7.83(m,2H),7.80- 7.74(m,2H),7.61(dd,J=8.9,2.4Hz,2H),7.41(dd,J=8.6,1.8Hz,4H),7.37-7.25(m,8H), 7.21-7.10(m,6H),6.82-6.79(m,2H),6.78-6.73(m,2H),6.68-6.61(m,2H),6.42(dt,J=7 .5,1.4Hz,2H),1.36(d,J=16.8Hz,54H).MALDI-MS(m / z):calcd.1341.72found.1341.71.
[0041] Example 2
[0042] Preparation of compound 2
[0043] The synthetic route of compound 2 of the present invention is as follows:
[0044]
[0045] The specific synthetic route of compound 2 of the present invention is as follows:
[0046] Compound 2a (5g, 15.68mmol), compound 2b (5.24g, 31.36mmol), and cesium carbonate (15.33g, 47mmol) were dissolved in 200mL N,N-dimethylformamide solution, heated to 120°C under nitrogen protection, and stirred for one night. After cooling to room temperature, 300mL of deionized water was added to the mixture, stirred for 10min, and a white precipitate appeared. The white precipitate was obtained by suction filtration using a Buchner funnel, and the precipitate was transferred to a beaker, a little methanol was added, and slurry was made for 20min. After suction filtration, vacuum drying was performed for 8h to obtain a white solid compound M3 (11.5g, 87%).1 H NMR (400MHz, CDCl3) δ8.15(d,J=7.6Hz,4H),7.98(d,J=0.8Hz,2H),7.50(t,J=7.8H z,4H),7.32(t,J=7.8Hz,4H).7.19(d,J=8.0Hz,4H)MALDI-MS(m / z):calcd.611.97 found.611.93.
[0047] Under nitrogen, compound M3 (1 g, 1.63 mmol), compound 2c (0.54 g, 1.63 mmol), tris(dibenzylideneacetone)dipalladium (22 mg, 0.03 mmol), DPPF (27 mg, 0.05 mmol), sodium tert-butoxide (0.23 g, 2.38 mmol) were dissolved in 50 mL of toluene, heated to 80°C, stirred at 80°C for 12 h, and then cooled to room temperature. The mixture was filtered through diatomaceous earth and silica, and concentrated under reduced pressure. The concentrate was purified by silica gel column chromatography (dichloromethane / petroleum ether=1 / 4, v / v) to obtain a white solid M4 (0.45 g, 36%). 1 H NMR (400MHz, CDCl3) δ8.16-8.07(m,4H),7.76-7.62(m,4H),7.60-7.43(m,5H),7.35-7.20(m, 7H),7.12-7.06(m,8H),6.70-6.50(m,4H),6.39-6.30(m,2H).MALDI-MS(m / z):calcd.815.19 found.815.15.
[0048] Compound M4 (0.4 g, 0.48 mmol), compound 2d (0.24 g, 0.48 mmol), Pd(PPh3)4 (14 mg, 0.01 mmol), potassium carbonate (0.11 g, 0.77 mmol) were dissolved in a mixed solvent of tetrahydrofuran and water (20 mL: 5 mL), heated to 80 ° C under nitrogen protection, and stirred for 24 h. After cooling to room temperature, 50 mL of deionized water was added to the mixture, and the reaction mixture was extracted with dichloromethane (3×50 mL), dried over anhydrous sodium sulfate, and the solvent was removed by distillation under reduced pressure. The residue was separated and purified by silica gel column chromatography (petroleum ether / dichloromethane=5 / 1, v / v) to obtain white solid compound 2 (0.38 g, 71%). 1H NMR(400MHz, CDCl3)δ8.48(d,J=2.5Hz,2H),7.96-7.90(m,4H),7.89-7.85(m,2H), 7.81-7.73(m,2H),7.62(dd,J=9.0,2.5Hz,2H),7.42(dd,J=9.0,1.8Hz,4H),7.39- 7.26(m,8H),7.23-7.12(m,10H),6.80-6.76(m,2H),6.79-6.72(m,2H),6.69-6.62 (m,2H),6.43(dt,J=7.5,1.4Hz,2H),1.34(s,18H).MALDI-MS(m / z):calcd.1117.47 found.1117.49.
[0049] Example 3
[0050] The optimal geometrical configuration of the compound 1 in Example 1 was calculated by quantum chemical simulation based on the B3LYP / def2SVP basis set. Figure 1 It can be seen that the torsion angle between the MR skeleton and the benzene bridge of compound 1 is 56.55°, and the torsion angle between the carbazole group and the benzene bridge is 66.44°. Due to the cross-conformation characteristics of the spirofluorene structure, the spirofluorene and the adjacent unit plane present a vertical conformation with a torsion angle of 90.56°. The stereo coating of the carbazole group effectively prevents the aggregation of molecules.
[0051] Example 4
[0052] DFT and TD-DFT calculations were performed on compound 1 in Example 1 on the B3LYP / def2SVP basis set to obtain the frontier orbital distribution, energy level arrangement, SOC and NTO of compound 1. Figure 2 It can be seen that the energy levels of the S1 state and the S2 state of compound 1 are almost parallel, and there is a competitive relationship between the S1 state and the S2 state. The S1 state has CT characteristics, while the S2 state has MR characteristics. From the SOC, it can be seen that there is a multi-channel anti-system crossing process between the energy levels.
[0053] Example 5
[0054] Compound 1 in Example 1 was heated at a rate of 20°C / min in the range of 30-700°C under N2 protection, and a thermogravimetric curve was obtained. Figure 3 It can be seen that the temperature at which compound 1 decomposes 5% is 459°C, indicating that the material has good thermal stability.
[0055] Example 6
[0056] The compound 1 in Example 1 was dissolved in a toluene solution (10 -5M), the UV-visible absorption spectrum, photoluminescence spectrum and low-temperature fluorescence phosphorescence spectrum of compound 1 in toluene solution at room temperature were measured. Figure 4 (a) It can be seen that compound 1 exhibits a strong absorption band below 350nm, which can be assigned to the π→π* and n→π* transitions of the donor fragment and the oxygen-bridged triarylamine fragment, as well as an absorption band near 380nm mainly from the ICT effect. The emission peak of compound 1 in solution is 410nm, and the emission peak in the film is 408nm. A narrow FWHM of 30nm is obtained in both the solution and the film. The low-temperature fluorescence and phosphorescence spectra of compound 1 were measured in 77K toluene solution. Figure 4 (b) It can be seen that the ΔE of compound 1 ST It is 0.24eV.
[0057] Example 7
[0058] The UV-visible light absorption performance of compound 1 in Example 1 was tested in different solutions. Compound 1 was dissolved in n-hexane, toluene, butyl ether, isopropyl ether, ethyl ether, ethyl acetate, tetrahydrofuran, N,N-dimethylformamide, acetone and acetonitrile solutions (all at a concentration of 10 -5 M), and tested its UV-visible light absorption properties in different solutions, such as Figure 5 As shown in the figure, as the polarity of the solvent increases, the UV-visible absorption spectrum of the compound does not change significantly.
[0059] Example 8
[0060] The photoluminescence performance of compound 1 in Example 1 was tested in different solutions. Compound 1 was dissolved in n-hexane, toluene, butyl ether, isopropyl ether, ethyl ether, ethyl acetate, tetrahydrofuran, N,N-dimethylformamide, acetone and acetonitrile solutions (all at a concentration of 10 -5 M), and tested its photoluminescence spectra in different solutions, such as Figure 6 As shown. It was found that the compound showed obvious bimodal emission as the solvent polarity increased, and exhibited a narrow band emission of about 410nm in low polarity solvents (from n-hexane to ether), which means that the radiation transition mainly occurred in the MR unit. With the continuous increase in solvent polarity (from ethyl acetate to dichloromethane), a wide FWHM CT peak appeared at a long wavelength, and the peak was continuously red-shifted and FWHM broadened in a strong polar solvent (from acetone to acetonitrile). This phenomenon shows that compound 1 has two different radiation transition pathways (S1→S0 and S2→S0), which is consistent with the theoretical calculation results of Example 4.
[0061] Example 9
[0062] The fluorescence lifetime of compound 1 in Example 1 in a 1% doped mCPCN film was tested under a nitrogen atmosphere. Figure 7 As shown, compound 1 exhibits a delayed fluorescence component of nanoseconds and a delayed fluorescence component of microseconds. The short lifetime of compound 1 is 0.37ns and the long lifetime is 0.25μs, which indicates that the material has TADF characteristics.
[0063] Example 10
[0064] The application of compound 1 in Example 1 in an organic electroluminescent device. The compound is used as a guest material of the light-emitting layer to prepare an organic electroluminescent diode having a structure of ITO / PEDOT:PSS (40nm) / mCPCN:x wt% emitter (25nm) / TmPyPB (45nm) / LiF / Al. Among them, PEDOT:PSS is a hole injection layer, mCPCN is a main material of the light-emitting layer, TmPyPB is an electron transport layer, LiF is an electron injection layer, and Al is a cathode. Figure 8 As shown, at a doping concentration of 1 wt%, the compound 1 doped device achieved the best electroluminescent performance, and its maximum external quantum efficiency was 9.61%. The electroluminescent performance parameters of the doped device of this embodiment are recorded in Table 1.
[0065] Table 1 Electroluminescent performance parameters of compound 1 doped devices in the embodiments of the present invention
[0066]
[0067] Embodiment 11
[0068] The electroluminescence spectrum of compound 1 in Example 1 in an organic electroluminescent device. Fig. 9 As shown, at doping concentrations of 0.5%, 1% and 2%, the doped device of compound 1 shows blue-violet light emission with an emission peak of 410nm. Even at high doping, it can maintain an extremely narrow half-peak width, which will be beneficial to high-definition display.
[0069] Example 12
[0070] The two compounds prepared in the examples were dissolved in toluene to prepare 10 -5 M solution, and tested its photoluminescence spectrum, half-peak width, quantum efficiency, and lifetime. The photophysical parameters of compound 1-2 of this example are recorded in Table 2.
[0071] Table 2 Photophysical parameters of compound 1-2 in the examples of the present invention
[0072]
[0073] Although the present invention has been described in conjunction with the preferred embodiments, the present invention is not limited to the above embodiments, and it should be understood that the appended claims summarize the scope of the present invention. Under the guidance of the inventive concept, those skilled in the art should be aware that certain changes made to the various embodiments of the present invention will be covered by the spirit and scope of the claims of the present invention.
Claims
1. A type of anti-Kasha rule narrow-band blue-violet TADF material, characterized by: The chemical structure of narrow-band blue-violet TADF material is shown in formula (1): The R's are each independently selected from hydrogen or tert-butyl.
2. The anti-Kasha rule narrow-band blue-violet TADF material according to claim 1, characterized in that: Narrow-band blue-violet TADF materials have one of the following chemical structures:
3. The use of the anti-Kasha rule narrow-band blue-violet TADF material according to claim 1 or 2, characterized in that: Narrow-band blue-violet TADF materials are used as luminescent materials in organic electroluminescent devices to prepare blue-violet OLEDs.
4. The use of the anti-Kasha rule narrow-band blue-violet TADF material as claimed in claim 3, characterized in that: The narrow-band blue-violet TADF material is used as the guest material of the light-emitting layer to prepare the light-emitting layer.
5. The use of the anti-Kasha rule narrow-band blue-violet TADF material according to claim 4, characterized in that: The doping concentration of the narrow-band blue-violet light TADF material in the main material of the light-emitting layer is 0.5-2wt%.
Citation Information
Patent Citations
Thermally activated delayed fluorescence material, organic light emitting device, and display / illumination device
CN111454263A
Spiroacridine compound and application thereof
CN113105456A